A state-of-art review of Loricariidae (Ostariophysi: Siluriformes) cytogenetics - Francisco de Menezes Cavalcante Sassi; Marcelo de Bello Cioffi; Orlando Moreira-Filho (Neotropical Ichthyology)
Abstract Loricariidae is a Neotropical fish family divided into six subfamilies and ranking in third among the most biodiverse fish groups. This study conducts an updated review of the cytogenetic investigations within the family, discussing the trends in chromosomal evolution and the main gaps and future directions for studies. Covering 125 publications that analyzed 234 species from all subfamilies except Lithogeninae, corresponding to about 21% of the valid species diversity, our study revealed samples from six different river basins in Argentina, Brazil, Ecuador, Paraguay, and Venezuela. There was a dearth of data for northeast Brazil, the Western Amazon, the Guianas Shield, and other Neotropical countries. In loricariids, there are seven different sex chromosome systems and a variety of diploid numbers (2n) ranging from 33 to 96 as a result of different chromosomal rearrangements such as fusions, fissions, translocations, and inversions. We recorded more simple nucleolar organizer regions (Ag-NOR) compared to multiple ones, and the fundamental number (FN) varied between 34 and 142. Populational studies have been conducted only in a few taxa, but a remarkable karyotype variation that includes B chromosomes is shown. Despite continuous efforts, cytogenetics still does not adequately capture the diversity of Loricariidae.